MAKNA HIJRAH BAGI KALANGAN REMAJA NON SANTRI: DAMPAK PENGGUNAAN MEDIA SOSIAL - Syahrin, Alif Alfi; Mustika, Bunga (IAIN Palangka Raya, 2020)
Various kinds of religious contents were widely circulated in social media with various kinds of covers to attract users, especially the millennial generation as active users of social media. Especially for non-santri teenagers who had a high curiosity in religious insight. The method used was a qualitative research with descriptive research. Data collection techniques used were non-participant observation, in-depth interviews and documentation. The informants in this study were Muslim teenagers who were still studying. The findings indicated that their favorite social media were Instagram, What